2018
DOI: 10.4103/ejd.ejd_429_17
|View full text |Cite
|
Sign up to set email alerts
|

Oral health literacy and its determinants among adults in Southeast Iran

Abstract: Objectives:The present study aimed to assess oral health literacy level and its related factors among adult patients visiting Kerman Dental School.Materials and Methods:This cross-sectional study was conducted in Kerman Dental School clinic, among the first-time adult visitors. Individuals were selected randomly from volunteers who signed study consent forms. Background information and oral health literacy levels were acquired through the oral health literacy-adult questionnaire. Statistical analysis including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 13 publications
6
45
4
1
Order By: Relevance
“…Individuals with lower education and economic status had lower oral health literacy, contributing to poor access as they might not understand the importance of oral health and their options to access dental services. [ 35 , 36 ]. Our finding was in agreement with previous literature that reported health insurance to be an enabling factor for dental service utilisation [ 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with lower education and economic status had lower oral health literacy, contributing to poor access as they might not understand the importance of oral health and their options to access dental services. [ 35 , 36 ]. Our finding was in agreement with previous literature that reported health insurance to be an enabling factor for dental service utilisation [ 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used definition of oral health literacy is ''the degree to which individuals have the capacity to obtain, process, and understand basic oral health information and services needed to make appropriate oral health decisions'' [21]. This definition addresses the practical literacy of oral health and encompasses the focus on oral health information, guidance to healthcare systems, and active communication with health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The American Dental Association has confirmed that limited HL is an obstacle to the prevention, diagnosis and treatment of oral and dental illness, and clear, accurate and effective communication is one of the essential skills for effective dental practice [10]. There is strong evidence about the economic costs associated with the low level of oral and dental health literacy [11,12], and various studies have referred to the convergence between oral health and general health and the effects of poor oral health on quality of life [11,13,14]. So, there are many challenges in educating and helping people to obtain the necessary resources to make decision about oral and dental health.…”
Section: Introductionmentioning
confidence: 99%